2000
DOI: 10.1063/1.372901
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and underlayer thickness in SmCo/Cr films

Abstract: SmCo films with a Cr underlayer have been investigated as potentially attractive candidates for high density recording media. Magnetron sputtering was used here to produce Cr/SmCo x /Cr films on Si ͑100͒ substrates. The magnetic films were deposited at a substrate temperature of 350°C and an Ar pressure of 5 mTorr. Cr underlayers were deposited both at 25°C and at 350°C and exhibited different textures. Layer thicknesses were evaluated using Rutherford backscattering spectroscopy, while SmCo grain size and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…The scaling of the magnetic forces can be explained as follows. The magnetic dipole field ͑stray field͒ of a magnet B ϳ 0 mr −3 is scale invariant-the magnetic moment m of an element of magnetization M scales as k −3 , whereas the magnetic field B falls off as r −3 , which scales as k 3 . However, the magnetic moment of a coil, m coil ϳ IA ϳ jaA where a is the conductor cross section and A is the coil area, scales as k −4 , hence the magnetic field scales as k −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The scaling of the magnetic forces can be explained as follows. The magnetic dipole field ͑stray field͒ of a magnet B ϳ 0 mr −3 is scale invariant-the magnetic moment m of an element of magnetization M scales as k −3 , whereas the magnetic field B falls off as r −3 , which scales as k 3 . However, the magnetic moment of a coil, m coil ϳ IA ϳ jaA where a is the conductor cross section and A is the coil area, scales as k −4 , hence the magnetic field scales as k −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Singh 等人 [15] 的研究表明, PLD 法制备 SmCo 薄膜中, 低的沉积速 [16][17][18][19][20] . 近年来, 一些工作报道了 Cr 层厚度对 SmCo/Cr 薄膜磁性能的影响 [21,22] , 我们通过实验研究了 Cr 缓 冲层厚度对 SmCo/Cu 薄膜磁性和结构的影响, 如图…”
Section: 实验结果和分析unclassified
“…Lots of efforts have been put into the research about the sputtered SmCo-based films [4][5][6][7][8][9][10]. It is found that the SmCo-based films prepared by conventional sputtering and subsequent annealing process are almost amorphous and the crystallization is hard to be completed, which decides that the magnetic properties of these SmCo-based films are insensitive to heat treatment [4,5].…”
Section: Introductionmentioning
confidence: 98%